The smart IOT earth leakage circuit breaker with transformerless and SMPS auto recloser - Sim, Sy Yi; Hud, Muhammad Haziq; Mohd Noh, Faridah Hanim; Norjali, Rasida; Sahari, Norain; Zulkifli, Mardzulliana; Mashori, Sumaiya; Law, Kah Haw (FAZ Publishing, 2020)
Earth leakage Circuit Breaker (ELCB) is function as a protection device that shall install either in industrial or residential protect electrical appliance or user from electrical shock or current leakage. When ELCB fault is detected, mechanical switch trigger the system to trip the circuit breaker. The problem faced by the user are the need to access to distribution box (DB) when tripping occur to turn it on manually. Some home appliance such as computer and alarm system should always connected to supply to prevent data from crashing or system mulfunction. The Smart Internet of Thing (IOT) Earth Leakage Circuit Breaker with Transformerless and SMPS Auto Recloser is proposed in this project to solve the need of always standby near to the DB to turn on after trip. This project has been improved from previous study with some transformation of circuit and prototype design. Transformerless circuit develop on this project eliminated the need of bulky transformer which usually used on linear circuit to power the microcontroller for control system to automatically recloser ELCB. Microcontroller used on this project are ESP32 module link with the IoT module to access from another location within the range. The Switch Mode Power Supply (SMPS) circuit is design to power DC motor in order to recloser the ELCB. The transformerless and SMPS is designed in two separate circuit to prevent microcontroller from damage while starting the DC motor. The auto recloser is set for 15 time tripping to prevent continuously fault that protect wiring and appliance from danger.